(untitled) (The International Research Journal of Management Science, 2025)
Purpose: This study examines the impact of Perceived Risk (PR) on Online Shopping Behavior (OSB) among Generation Z in Nepal, focusing on the mediating role of Digital Literacy (DL). Methodology: A descriptive and explanatory research design with a quantitative research approach was employed. The population comprised Generation Z individuals in Nepal. Using purposive sampling, after data screening, 395 valid responses were retained for analysis. Data were analyzed using SmartPLS, incorporating higher-order constructs (HOC) for PR and applying reliability and validity checks based on threshold values. Findings: The analysis revealed significant relationships between PR dimensions and online shopping intention, with DL playing a partial mediating role. Higher digital literacy levels were found to mitigate the negative impact of PR on OSB. Implications: The findings provide insights for e-commerce platforms and policymakers to design strategies that enhance DL, thereby reducing PR and encouraging online shopping among younger consumers. Originality/Value: This study uniquely combines a HOC Perceived Risk with the mediating role of DL within the context of Generation Z in Nepal.